2017
DOI: 10.1016/j.fsi.2017.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two glutathione S-transferases from freshwater bivalve Anodonta woodiana : Chronic effects of pentachlorophenol on gene expression profiles

Abstract: Glutathione S-transferases (GST) play a prominent role in protecting cells against oxidative stress. Our previous study showed that the reactive oxygen species (ROS) generated from pentachlorophenol (PCP) could cause an acute impact on freshwater bivalve Anodonta Woodiana, but its chronic toxicity remain unclear. In order to investigate the chronic effect of PCP, clams A. Woodiana were randomly grouped into PCP treated group in which animals were administrated with 13.9 μg/L concentrations of PCP, and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
3
0
3
Order By: Relevance
“…Thulasi et al reported that COX and mitochondrial-like proteins could be associated with mitochondrial membrane damage due to the high levels of ROS production under severe oxidative stress induced by food deprivation. , The mtMnSODs, key antioxidant enzymes that contain manganese, can catalyze anion disproportionation and have been reported to be involved in the innate immune response of crabs. , They are considered the first line of defense against oxidative stress induced by excessive ROS beyond the threshold limits resulting from respiratory bursts . A GST catalyzes the conjugation of glutathione (GSH) with toxic reactive metabolites and is considered a detoxification enzyme against the chemotoxicity of xenobiotics . Moreover, GST-θ was assumed to eliminate the ROS and reduce the oxidative damage owing to its specific serine residue. , The regulation of these DEPs in crab muscle indicated oxidative stress in crabs caused by excess production of ROS during transportation due to severe temperature fluctuations, anoxic environments, and bacterial infections …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thulasi et al reported that COX and mitochondrial-like proteins could be associated with mitochondrial membrane damage due to the high levels of ROS production under severe oxidative stress induced by food deprivation. , The mtMnSODs, key antioxidant enzymes that contain manganese, can catalyze anion disproportionation and have been reported to be involved in the innate immune response of crabs. , They are considered the first line of defense against oxidative stress induced by excessive ROS beyond the threshold limits resulting from respiratory bursts . A GST catalyzes the conjugation of glutathione (GSH) with toxic reactive metabolites and is considered a detoxification enzyme against the chemotoxicity of xenobiotics . Moreover, GST-θ was assumed to eliminate the ROS and reduce the oxidative damage owing to its specific serine residue. , The regulation of these DEPs in crab muscle indicated oxidative stress in crabs caused by excess production of ROS during transportation due to severe temperature fluctuations, anoxic environments, and bacterial infections …”
Section: Resultsmentioning
confidence: 99%
“…36 A GST catalyzes the conjugation of glutathione (GSH) with toxic reactive metabolites and is considered a detoxification enzyme against the chemotoxicity of xenobiotics. 37 Moreover, GST-θ was assumed to eliminate the ROS and reduce the oxidative damage owing to its specific serine residue. 35,38 The regulation of these DEPs in crab muscle indicated oxidative stress in crabs caused by excess production of ROS during transportation due to severe temperature fluctuations, anoxic environments, and bacterial infections.…”
Section: Validation Of Tmt-based Proteomics Approachesmentioning
confidence: 99%
“…Пресноводные моллюски играют важную роль в экосистемных процессах благодаря их влиянию на циклирование питательных веществ, биотурбацию и осаждение взвешенной органики (Vaughn, 2010). К сожалению, места их обитания все чаще страдают из-за стоков различных загрязнителей (Liu et al, 2017). Изменения в среде обитания приводят к быстрым изменениям в метаболизме пресноводных моллюсков на разных уровнях: биохимическом, клеточном и физиологическом.…”
Section: рис 1 схема развития процессов образования продуктов перекunclassified
“…и Unio spp., предложены в качестве чувствительных объектов в биомониторинге, биоиндикации и биотестировании (Guidi et al, 2010). Исследования выявили способность представителей рода Anodonta (на примере A. woodiana) аккумулировать микроэлементы и пестициды, а также их потенциал для обнаружения мутагенов (Liu et al, 2017). Из данных литературы известно, что униониды рода Anodonta (на примере A. imbecilis) также высокочувствительны к тяжелым металлам, как и зоопланктон (Daphnia), и более чувствительны, чем рыбы и водные насекомые (Keller & Zam, 1991).…”
Section: рис 1 схема развития процессов образования продуктов перекunclassified
See 1 more Smart Citation